SENSITIVITY TO ANTIBIOTICS AMONG STRAINS OF SALMONELLA CURRENT, WHICH CIRCULATES IN THE PAST 10 YEARS IN UKRAINE - Bubalo, V. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
In this article the main results of the sensitivity to antibiotics on S. Typhimurium, S. strains of Salmonella Enteritidis and rare groups that circulate in Ukraine last 10 years were described. The unifying disc-fusion method determined the sensitivity of Salmonella strains to several antibiotics. Resistance to antibiotics of strains of Salmonella was caused by the lack of effective influence of drugs on salmonellosis. The obtained results revealed antibiotics with a strong antimicrobial action and a narrow focus on strains of Salmonella.